Inhibition and the stimulus control of operant behavior - Hearst, Eliot (1970)
A variety of methods, definitions, and theoretical notions that have been used in the study of inhibitory stimulus control were reviewed and evaluated. Preliminary data from several new operant methods were also described. It was proposed that future workers distinguish clearly between two forms of inhibitory control: (a) the learned power of a specific stimulus to reduce behavior, and (b) a dimensional effect, in which responding increases as values progressively more distant from the value of that specific stimulus along some dimension are presented (generalization gradient). Conclusions from several important recent studies were shown to be strongly dependent on the individual experimenter's criterion for deciding when a stimulus is inhibitory. The concept of inhibition seems a very valuable one for the field of operant behavior, and it deserves more attention than it has received in the past.